Analisis Yuridis terhadap Keabsahan Klausul Masa Percobaan dalam Perjanjian Kerja Waktu Tertentu (Pkwt) di Sektor Pelayaran dan Implikasinya terhadap Perlindungan Hak Pekerja: Studi Putusan No 108/Pdt.Sus-Phi/2023/Pn Medan - Fauza Nahwa Salsabila Siregar (Jurnal Hukum Lex Generalis, 2026)
This study examines the validity of probationary clauses in Fixed-Term Employment Agreements (PKWT) within the maritime shipping sector based on Decision No. 108/Pdt.Sus-PHI/2023/PN Medan. The findings indicate that probationary clauses in PKWT violate Article 58 of the Indonesian Labor Law and are therefore invalid. Maritime law does not specifically regulate probationary periods, making labor law applicable. Judicial considerations differ, with the Medan District Court emphasizing freedom of contract, while Decision No. 289 K/Pdt.Sus-PHI/2024 affirms the prohibition of probationary periods in PKWT as a mandatory legal provision.